Research on Wetting-Drying Cycles’ Effect on the Physical and Mechanical Properties of Expansive Soil Improved by OTAC-KCl - Bao-tian Wang; Can-hong Zhang; Xue-lian Qiu; En-yue Ji; Wen-hui Zhang (Advances in Materials Science and Engineering)
Expansive soil experiences periodic swelling and shrinkage during the alternate wet and dry environments, which will result in severe damage to the slope stability. In this study, a promising modifier OTAC-KCl is introduced, which has a good diffusivity and is soluble in water or other solvents easily. Firstly, a reasonable combination of ameliorant 0.3% STAC and 3% KCl is chosen referring to the free swell test. Then, the best curing period, 14 days, is gotten from UCS tests. The effect of wetting and drying cycles on engineering properties of expansive soil improved by OTAC-KCl admixtures after 14-day curing is also studied accordingly. Both treated and untreated expansive soil samples are prepared for the cyclic wetting-drying tests which mainly include cyclic swelling potential and cyclic strength tests. Experimental results show that the swelling potential of expansive soil samples stabilized with OTAC-KCl is suppressed efficiently, and the untreated soil specimens will collapse when immersed in water while the treated specimens keep in good conditions. Moreover, expansive soil samples modified with 0.3% OTAC + 3% KCl show enough durability on the swelling ability, shear strength, and unconfined compressive strength, which means, that both the physical and the mechanical properties of stabilized expansive soil have been improved effectively.